Faktor-Faktor yang Mempengaruhi Cash Holding - Ramadhan Aldino (2021)
This study aims to determine the effect of ownership concentration, independent commissioners, net working capital, leverage, and cash flow on cash holding in 150 manufacturing sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research is a type of quantitative research using secondary data in the form of the company's annual report. The Fixed Effect Model (FEM) with panel data regression was used in this study using STATA version 16. Based on the test results and analysis, it can be concluded that ownership concentration and independent commissioners has no effect on cash holding, while net working capital, leverage, and cash flow have a significant positive effect on cash holding. The results of this study have implications for companies, regulators and future researchers.